Water infiltration in urban soils and its effects on the quantity and quality of runoff - Yang, Jin-Ling; Zhang, Gan-Lin (Journal of soils and sediments, 2011)
Purpose Urban soil characteristics, especially soil physical properties, are subject to dramatic changes due to compaction by intensive human activities, which may cause frequent flood events during the rainy seasons. The aim of this study was to explore the water infiltration characteristics of urban soils with different degrees of compaction and to determine the effects of infiltration on environmental problems in urban areas. Materials and methods Ten typical land use patterns with various vegetation and age were selected in Nanjing City, China to determine the infiltration rates by the dual-ring method. Three replicated sites were done in the same combined mode. At the same time, other soil physical and chemical properties that may affect infiltration rate were also determined. In addition, urban surface runoff coefficients were estimated according to final infiltrations and rain intensities in the different degrees of soil compaction. The quality of flood water from a strong rainstorm in a main road in Nanjing was analyzed. Results and discussion The final infiltration rates of urban soils were highly variable (from very slow to very fast). Low soil infiltration rates are related to many factors; however, urban soil compaction is the leading one. Infiltration rates decreased with an increase in the bulk density and with a reduction in the air-filled porosity. Thus, large amounts of macropores increase the infiltration rate and reduce surface runoff. Runoff coefficients of compacted soils with low infiltration rates were high, especially for extremely compacted soil. As a result, the prevalence of flooding is high in compacted soils, and the quality of surface runoff water is reduced during flooding events. The concentrations of NO 3 − -N, total nitrogen, molybdate-reactive phosphorus, total phosphors, and suspended material in urban surface runoff were significantly higher than those observed in forested or agricultural watersheds. Conclusions In urban areas, low infiltration rates caused by soil compaction have negative effects on the eco-environment of the city and result in increased instantaneous flooding and poor surface water quality. Thus, to improve the eco-environment of urban areas, the amount of greenbelt soil must be increased and soil compaction must be reduced.